Identification Content of the Red Dragon Fruit Extract Skin Using Fourier Transform Infrared (FTIR) and Phytochemistry - Muhammad Ilham Noor; Evi Yufita; Zulfalina . (Journal of Aceh Physics Society, 2016)
Corrosion is a decline in the quality of the metal due to electrochemical reaction between the metal by a corrosive medium. One effort to reduce the rate of corrosion is by adding inhibitors. Organic inhibitors that can be used include antioxidants and vitamin C. To determine both the content of the test method is used Fourier Transform Infrared (FTIR) and phytochemicals. FTIR is a method to measure used to determine the group and the type of bonding of a compound based on the value of the wave number of a plant. Phytochemical screening is a test of the qualitative secondary metabolites biologically active compounds found in plants. In this study used a sample of red dragon fruit. The results of the analysis provide information regarding the types of biologically active compounds and levels of the active compound contained in the red dragon fruit.